Propozycja warsztatów doskonalących kompetencje edukatorów = A proposal for workshops improving educators` competences - Famuła-Jurczak, Anita; Kurian-Harkowiec, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Increasing the effects of the educational process is very important nowadays. The workshop proposal presents general goals, methods, teaching resources and course of classes improving educators? competences in conflict management.
Keywords: kompetencje społeczne; konflikt; social competences; conflict